Biologically Targeted Magnetic Hyperthermia: Potential and Limitations - Chang, David; Lim, May; Goos, Jeroen A. C. M.; Qiao, Ruirui; Ng, Yun Yee; Mansfeld, Friederike M.; Jackson, Michael; Davis, Thomas P.; Kavallaris, Maria (Frontiers in Pharmacology, 2018)
Hyperthermia, the mild elevation of temperature to 40-43°C, can induce cancer cell death and enhance the effects of radiotherapy and chemotherapy. However, achievement of its full potential as a clinically relevant treatment modality has been restricted by its inability to effectively and preferentially heat malignant cells. The limited spatial resolution may be circumvented by the intravenous administration of cancer-targeting magnetic nanoparticles that accumulate in the tumor, followed by the application of an alternating magnetic field to raise the temperature of the nanoparticles located in the tumor tissue. This targeted approach enables preferential heating of malignant cancer cells whilst sparing the surrounding normal tissue, potentially improving the effectiveness and safety of hyperthermia. Despite promising results in preclinical studies, there are numerous challenges that must be addressed before this technique can progress to the clinic. This review discusses these challenges and highlights the current understanding of targeted magnetic hyperthermia.